2009
DOI: 10.1016/j.juro.2009.07.068
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study on the Perineal Versus Penoscrotal Approach for Implantation of an Artificial Urinary Sphincter: Cuff Size and Control of Male Stress Urinary Incontinence

Abstract: There appears to be a higher completely dry rate with fewer subsequent tandem cuff additions with the perineal approach compared to the penoscrotal approach. This disparity may be explained by a more proximal artificial urinary sphincter cuff placement in the perineal group as evidenced by a larger cuff size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 17 publications
4
32
0
3
Order By: Relevance
“…In a retrospective 4-center study by the same working group, postoperative complication rates of 49 patients were analyzed. The authors found slightly lower total complication rates after penoscrotal compared to initial perineal AUS implantation [12]. However, in the above-mentioned studies, complications included only device malfunction, erosion/infection, and urethral atrophy rates.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective 4-center study by the same working group, postoperative complication rates of 49 patients were analyzed. The authors found slightly lower total complication rates after penoscrotal compared to initial perineal AUS implantation [12]. However, in the above-mentioned studies, complications included only device malfunction, erosion/infection, and urethral atrophy rates.…”
Section: Discussionmentioning
confidence: 99%
“…For male patients, the data do not agree upon a preferred surgical technique. Henry et al report improved continence rates with the perineal approach, while other data demonstrate similar outcomes with either a penoscrotal or perineal approach [32,33]. They hypothesize that the more proximal cuff placement afforded by the perineal could account for their outcomes [32].…”
Section: Incontinencementioning
confidence: 98%
“…Henry et al report improved continence rates with the perineal approach, while other data demonstrate similar outcomes with either a penoscrotal or perineal approach [32,33]. They hypothesize that the more proximal cuff placement afforded by the perineal could account for their outcomes [32]. In the pediatric population, the cuff is most commonly placed at the bladder neck and often the intrinsic compression from the cuff, without activation or cycling, is adequate to provide enough resistance for continence.…”
Section: Incontinencementioning
confidence: 99%
“…The transscrotal approach for implantation of an AUS is reportedly more rapid and easier than the traditional perineal incision. Nonetheless, some authors have reported a higher completely dry rate and fewer tandem cuff additions with the perineal approach, a finding they attribute to the more proximal placement of the AUS cuff [40,41].…”
Section: Prb For the Ausmentioning
confidence: 99%